Come costruirsi un grigliato NTv2 in casa - Ernesto Sferlazza (GEOmedia, 2014)
For those working with spatial data in a geographic information system (GIS), one of the most frequent activities (and, not infrequently, even frustrating) concerns the transformation of coordinates between different reference systems.